Japanese Fusion Materials Development Path to DEMO. (3rd October 2017) - Muroga, Takeo; Tanigawa, Hiroyasu
Abstract: This paper reports Japanese strategy for developing blanket structural materials for DEMO. In the Japanese program, the candidate materials are categorized into Primary Option (RAFM) and Advanced Options (V-alloy, SiC/SiC, ODS-RAFM etc.). A staged development is planned corresponding to the three decision-making points (DPs), DP1: Intermediate check and review (C&R), DP2: Decision of transition of research and development (R&D) focus to DEMO, and DP3: Decision of DEMO construction. The near-term D-Li neutron source (A-FNS) and IFMIF are regarded as key facilities for the development. The strategy emphasizes "standardization" as an important step toward DEMO design qualification and licensing. The procedure to standard materials specifications by way of establishing structural design criteria and materials property requirements, and the procedure's interaction with the schedule of irradiation data acquisition are discussed.